Critical library instruction : theories and methods - Accardi, Maria T.; Drabinski, Emily; Kumbier, Alana (Library Juice Press, 2010)
"A collection of articles about various ways of applying critical pedagogy and related educational theories to library instruction"--Provided by publisher.